Out-of-time-order correlators as a measure of quantum chaos for sinai, cardioid and diamond billiards - Ador, Tasnim Anzum; Farid, Nayeem (Brac University, 2023)
This thesis is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Science in Physics.